Fertilização mineral em Eucalyptus dunnii Maiden: efeitos nos estoques dos nutrientes - Dick, Grasiele (2018)
Improving the management of mineral fertilization is essential to the maintenance of productive capacity and nutritional sustainability of soils destined to forestry with fast growing tree species. The objective of this study was to evaluate the effects of different mineral fertilization recommendations on soil nutrient stocks, productivity, biomass production, nutrient and carbon allocation, and estimate the nutritional balance (NB) in Eucalyptus dunnii. The study was developed at the Ponta das Canas site, São Gabriel, Rio Grande do Sul, Brazil. At 14 months of age, an area of 0.54 ha of the plot was delineated, which was subdivided into nine sample units of 20 m x 30 m each, in which were randomly added three replicates of different recommendations of N- P2O5-K2O (24:00:24), in coverage, which consisted of treatments T1 = standard fertilization (150 g plant-1); T2 = standard fertilization + 50% of the same dose (225 g plant-1) and T3 standard fertilization + 200% of the same dose (450 g plant-1). At 14 and 36 months after planting, soil samples were collected up to 80 cm deep and it can be seen that the pH was acid and the Ca and Mg contents were low to very low. The recommendation T3 combined with the residual effects of liming and pre-planting fertilization promoted an increase in soil nutrient contents and especially of K, P, Ca and Mg. The productivity, biomass production, accumulation of C and nutrients, indicated that, until the 36 months of age of Eucalyptus dunnii, the application of the T3 recommendation promoted higher tree height and, due to this variable, there was an increase in the volume per tree , compared to T1, however, the BHD did not differ between treatments. The amount of biomass and carbon was 58.7 Mg ha-1 and 26.9 Mg ha-1 respectively. Both did not vary according to the treatments and the tendency of biomass accumulation was: stem wood > branches > stem bark> leaves. Nutrient concentrations ranged between tree components, with higher leaf values and lower values in stem wood, and fertilization recommendations did not influence macronutrient concentrations. In the total biomass, there was an accumulation of 175.8; 25.4; 198.4; 231.6; 75.1 and 17.2 kg ha-1 of N, P, K, Ca, Mg and S, respectively. For B, Cu, Fe, Mn and Zn, the amounts were 391.5; 143.0; 2064.2; 12694.8 and 471.5 g ha-1, respectively. The inputs of nutrients via incident rainfall (Pt) were also evaluated and significant amounts of nutrients were incorporated into the aqueous solution, whose contribution sequence was K > S > Ca > N > Mg. These inputs could reduce the addition of 22% and 11% of the K and N doses, respectively, applied in pre-planting fertilization. The nutritional balance, considering the stem wood removal scenario of the Eucalyptus dunnii, is positive for nutrients N, P and K and negative for Ca, Mg and S, in all treatments. According to the results found, especially on productivity and biomass, in order to reduce operational costs and environmental impacts, the standard fertilization (150 g plant-1 of N-P2O5-K2O 24:00:24), in cover, can be recommended for plantations of Eucalyptus dunnii under site conditions similar to the present study.